The professor of the future: Perspectives of university faculty implementing Universal Design for Learning - Amy Accardo; Brie Morettini; Hind Alharbi; Kristen Prentice (To Improve the Academy, 2025)
Data show that the university student population is increasingly more diverse than in the past. Certainly, the conventional college student profile has evolved with approximately three out of every four students now falling into groups previously deemed nontraditional, including adult learners and first-generation students and students who identify as disabled and/or neurodivergent. Emerging throughout this shift in the university student population is a need to address university faculty uncertainty around how to support diverse and/or disabled learners. Despite the barriers to learning faced during the COVID-19 pandemic, there also arose the recognition by some U.S. faculty and staff that expanded college access provided as necessity, such as the use of educational technology and hybrid learning, supported access for a new and expanded population of students. As a result, university faculty and staff are uniquely open to frameworks guiding implementation of inclusive practices and pedagogy, such as Universal Design for Learning (UDL). Findings from the study nuance the conversations on implementation of UDL at the postsecondary level; particularly, the findings show that while professional development and support can assist faculty in understanding and implementing UDL, there is still resistance to widespread implementation. This work provides a roadmap to other institutions who wish to implement UDL and explores specific barriers—and potential solutions—to the strategic implementation of UDL.